2020
DOI: 10.1038/s41428-020-00408-4
|View full text |Cite
|
Sign up to set email alerts
|

Material design of nanocellulose/polymer composites via Pickering emulsion templating

Abstract: Cellulose nanofiber (CNF) is a crystalline fiber composed of a bundle of cellulose molecular chains and is expected to be used as a new biomass-derived nanomaterial. The CNF has a unique morphology: a few to tens of nanometer width and a submicrometer to micrometer length. Its application to various materials, in particular its utilization as a polymer reinforcing material, has been anticipated due to its excellent mechanical properties. However, CNFs and plastics are generally hard to mix, and thus, it is dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Morphology monitoring using CLSM revealed that orange fluorescence indicating acridine orange stained-CNFs lay at the surface of the dispersed phase, thereby stabilizing the oil droplets. This use of CLSM to confirm the template of the Pickering emulsion agent was also reported for zein particles stained with Nile blue A 5 , CNFs and nanocrystals stained with calcofluor white 35 , and nanocellulose stained with acridine orange 36 . Furthermore, CNFs affected the oil droplet size, indicating that CNFs had an important role in preventing the collision and aggregation of emulsion droplets by their accumulation at the oil–water interface.…”
Section: Discussionsupporting
confidence: 68%
“…Morphology monitoring using CLSM revealed that orange fluorescence indicating acridine orange stained-CNFs lay at the surface of the dispersed phase, thereby stabilizing the oil droplets. This use of CLSM to confirm the template of the Pickering emulsion agent was also reported for zein particles stained with Nile blue A 5 , CNFs and nanocrystals stained with calcofluor white 35 , and nanocellulose stained with acridine orange 36 . Furthermore, CNFs affected the oil droplet size, indicating that CNFs had an important role in preventing the collision and aggregation of emulsion droplets by their accumulation at the oil–water interface.…”
Section: Discussionsupporting
confidence: 68%
“…Morphology monitoring using CLSM revealed that orange fluorescence indicating acridine orange stained-CNFs lay at the surface of the dispersed phase, thereby stabilizing the oil droplets. This use of CLSM to confirm the template of the Pickering emulsion agent was also reported for zein particles stained with Nile blue A 5 , CNFs and nanocrystals stained with calcofluor white 35 , and nanocellulose stained with acridine orange 36 . Furthermore, CNFs affected the oil droplet size, indicating that CNFs had an important role in preventing the collision and aggregation of emulsion droplets by their accumulation at the oil-water interface.…”
supporting
confidence: 68%
“…Even though 3D-printable nanocellulose-based composites are still in their infancy, there has been an increase in their applications in different fields ranging from biomedicine, including wound dressing, drug release, and tissue engineering, sensors, food, and packaging, to energy storage and electronics, with growing interest in other areas as well [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], summarized in Figure 6 . This section discusses the recent development in 3D-printed nanocellulose-based composites for food, environmental, food packaging, energy, and electrochemical applications.…”
Section: Applications Of 3d-printed Nanocellulose-based Materialsmentioning
confidence: 99%
“…The combination of nanocellulose with other materials, polymers, and fillers can increase mechanical and thermal stability and change the wetting behavior of the native material [41]. For example, significant enhancement of cellulose tensile strength was achieved by loading cellulose with only 0.2% graphene [42].…”
Section: Functional Nanocellulose-based Composite Nanostructuresmentioning
confidence: 99%